Growth Inhibition, Residual Contact and Translaminar Toxicity of Annona-based Bioinsecticides on Tomato Leafminer: Laboratory and Greenhouse Assessments - Brito, Elaine Ferrari de [UNESP]; Lopes Baldin, Edson Luiz [UNESP]; Padoan Goncalves, Gabriel Luiz; Gimenes, Leila; Batista Fernandes, Joao; Ribeiro, Leandro do Prado (Springer, 2019)
This study aimed to evaluate the bioactivity of ethanolic extracts from different parts of some Annona species (A. montana, A. muricata and A. sylvatica) against T. absoluta. In the initial screening, the ethanolic extracts from leaves and seeds of A. muricata promoted pronounced lethality and growth inhibition of T. absoluta larvae by means of residual contact and translaminar action. However, these extracts did not affect its biology, oviposition in choice and no-choice tests, as well as egg viability. Afterwards, the crude ethanolic extracts of leaves and seeds from A. muricata were submitted to liquid-liquid partitioning, and their respective fractions were evaluated against T. absoluta larvae. These procedures disclosed the hydroalcoholic fraction from A. muricata seeds and both the ethyl acetate and dichloromethane fractions from its leaves as the most active against T. absoluta larvae. Then, proton nuclear magnetic resonance (H-1 NMR) experiments were performed aiming to identify the main constituents present in these fractions. The chemical analyses of each NMR spectrum revealed that A. muricata bioactive fractions presented acetogenins as major compounds. Moreover, a formulated ethanolic extract from A. muricata seeds presented similar bioactivity against T. absoluta larvae in both laboratory and greenhouse bioassays when compared with two commercial botanical insecticides (Anosom(TM) 1 EC and Azaamax 1.2 EC). Therefore, the seeds from A. muricata, discarded during the process of its fruit pulp extraction, are a potential source of bioactive acetogenins to formulate botanical insecticides to control populations of T. absoluta in tomato crops, mainly in organic production systems.
Keywords: Solanum lycopersicum; Tuta absoluta; Botanical insecticide; Annona spp; Acetogenins